Effects of extracorporeal shock wave on upper and lower limb spasticity in post-stroke patients: A narrative review. Issue 4 (6th June 2016) - Dymarek, Robert; Ptaszkowski, Kuba; Słupska, Lucyna; Halski, Tomasz; Taradaj, Jakub; Rosińczuk, Joanna
Abstract : Background: Effective treatment strategies for post-stroke muscle spasticity are still a significant interdisciplinary issue and challenge for neurologists, neurosurgeons, physiatrists nurses and physiotherapists. Extracorporeal shock wave (ESW) treatment is a well-supported physical modality used in a wide range of musculoskeletal disorders. The list of justified indications for ESW treatment and scientific areas of investigations is continuously evolving and adapting to different pathologies, including spasticity after stroke. Objectives: To analyze the relevant available research and clinical studies demonstrated that the treatment potentials and effectiveness of ESW procedure including mechanisms of the anti-spastic action within hypertonic muscles after stroke. Literature Search: A computer research was performed using MEDLINE, PubMed, PEDro, CINAHL, and EMBASE databases. Assessment of eligibility of papers was determined by two independent reviewers. The inclusion criteria comprised: publication in peer-reviewed journals, studies published in the last 10 years, involving clinical trials, full-version available and written in English only. Discussion: A total of 91 articles were collected, 83 of which were non relevant. Ultimately, 8 clinical studies within a total of 195 patients met inclusion criteria for this review. Only one randomized controlled trial was found and then scored using the Cochrane-based assessment. The other studies involving were analyzed separately according to their methodological quality in a descriptive manner. Conclusions: ESW was found to be safe and effective. The mechanism of ESW action is still under investigation.